Azorín, Castilla. Ed. de Juan Manuel Rozas. Labor, Barcelona, 1973; 220 pp. (THM, 21). - Frida Weber de Kurlat (Nueva Revista de Filología Hispánica, 1976)
Se reseñó el libro. Castilla. Ed. de Juan Manuel Rozas.